Seasonal updraft speeds change cloud droplet number concentrations in low-level clouds over the western North Atlantic - Kirschler, Simon; Voigt, Christiane; Anderson, Bruce; Campos Braga, Ramon; Chen, Gao; Corral, Andrea F.; Crosbie, Ewan; Dadashazar, Hossein; Ferrare, Richard A.; Hahn, Valerian; Hendricks, Johannes; Kaufmann, Stefan; et al. (Atmospheric Chemistry and Physics, 2022)
To determine the impact of dynamic and aerosol processes on marine low clouds, we examine the seasonal impact of updraft speed w and cloud condensation nuclei concentration at 0.43 % supersaturation ( NCCN0.43%) on the cloud droplet number concentration (NC) of low-level clouds over the western North Atlantic Ocean. Aerosol and cloud properties were measured with instruments on board the NASA LaRC Falcon HU-25 during the ACTIVATE (Aerosol Cloud meTeorology Interactions oVer the western ATlantic Experiment) mission in summer (August) and winter (February–March) 2020. The data are grouped into different NCCN0.43% loadings, and the density functions of NC and w near the cloud bases are compared. For low updrafts (w < 1.3 m s−1), NC in winter is mainly limited by the updraft speed and in summer additionally by aerosols. At larger updrafts (w > 3 m s−1), NC is impacted by the aerosol population, while at clean marine conditions cloud nucleation is aerosol-limited, and for high NCCN0.43% it is influenced by aerosols and updraft. The aerosol size distribution in winter shows a bimodal distribution in clean marine environments, which transforms to a unimodal distribution in high NCCN0.43% due to chemical and physical aerosol processes, whereas unimodal distributions prevail in summer, with a significant difference in their aerosol concentration and composition. The increase of NCCN0.43% is accompanied with an increase of organic aerosol and sulfate compounds in both seasons. We demonstrate that NC can be explained by cloud condensation nuclei activation through upwards processed air masses with varying fractions of activated aerosols. The activation highly depends on w and thus supersaturation between the different seasons, while the aerosol size distribution additionally affects NC within a season. Our results quantify the seasonal influence of w and NCCN0.43% on NC and can be used to improve the representation of low marine clouds in models.